ELEVATED URINARY NEOPTERIN SUGGESTS IMMUNE ACTIVATION IN ALZHEIMERS-DISEASE AND DOWNS-SYNDROME - Armstrong, R; Cattell, R; Jones, S; Winsper, S; Blair, J (1994)
Neopterin, an unconjugated pteridine, is secreted in large quantities by activated macrophages and can be used as a clinical marker of activated cellular immunity in a patient. Hence, neopterin levels were measured in urine samples taken from patients with Down's syndrome (DS), non hospitalised and hospitalised Alzheimer's disease (AD) and age and sex matched controls. All subjects and patients were free from infectious and malignant disease. A significant effect of age on urinary neopterin levels was found in control subjects, levels being greater in younger and older subjects. No significant trends with age were found in AD and DS patients. The mean level of neopterin was significantly increased in DS and AD compared with age matched controls suggesting immune activation in these patients. In DS, elevated neopterin levels were present in individuals at least 17 yrs old suggesting that immune activation could be associated with the initial deposition of β/A4 protein in the brain.